Foraging patterns of the Antarctic Shag Phalacrocorax bransfieldensis at Harmony Point, Antarctica - Casaux, Ricardo Jorge; Bertolin M.
During the 1995 and1996 summer seasons the foraging patterns of the Antarctic Shag Phalacrocorax bransfieldensis werestudied by direct observation at Harmony Point, Nelson Island, South ShetlandIslands. During pre-laying and incubation, individuals of both sexes usuallyforaged once a day, females early in the morning and males when their partnersreturned to their nests. Due to increasing energy requirements at the nest, rearingindividuals incremented the daily time invested in foraging activitiesdisplaying more, but shorter, foraging trips. The reduction in the duration ofthe foraging trips through the breeding season suggests that Antarctic shags budgettheir activities in order to buffer variable food abundance or energyrequirements at the nests. The possibility of using the foraging parametersconsidered in this study in ecosystem monitoring programmes is discussed. Fil: Casaux, Ricardo Jorge. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Centro de Investigación Esquel de Montaña y Estepa Patagóica. Universidad Nacional de la Patagonia "San Juan Bosco". Facultad de Ciencias Naturales - Sede Esquel. Centro de Investigación Esquel de Montaña y Estepa Patagónica; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Bertolin M. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina